Another Evening at Logos 1974, 79 & 81 - Logos ensemble; Eastley, Max; Feminist Improvising Group; Coum; Bailey, Derek (Ghent Logos Sub Rosa)
record 101 MAX EASTLEY + LOGOS ENSEMBLE 24'53Max Eastley + GodfrIed-WIllem Raes, MonIek Darge, Rob Keymeulen - 197902 FEMINIST IMPROVISING GROUP 25'38featuring GeorgIe Born, Lindsay Cooper, Maggie Nichols, Sally Potter, Irene Schweizer - 1979record 2 03 COUM+ LOGOS ENSEMBLE 21'36Genesis P.Orridge, Paul Woodrow, Cosey FannI Tutti, Joseph L/R Rose+ GodfrIed-WIllem Raes, Moniek Darge, Luk Houtkamp - 197404 DEREK BAILEY 20'42 Logos improvisations - 1981Never released before recordings from live sessions at Logos Foundation, Gent, Belgium (1974, 79 & 81), this is a start of a new series of vinyl only releases.Logos Foundation: Belgium Flanders' unique professional organisation for the promotion of new music and audio-related arts by means of new music production, concerts, performances, composition, technological research and other activities related to contemporary music. This organisation has been founded in 1968 by Godfried-Willem Raes and Moniek Darge.
Keywords: Improvisation